Potential in anti-cancer therapy using RNA - overview of therapies - Barbara Rusinowska (Kazimierz Wielki University, 2022)
The main targets for the production of mRNA-based tumor vaccines are tumor-associated antigens and tumor-specific neoepitopes exposed on the surface of tumor cells. Their mission is to stimulate the cellular response in the body of a sick patient. In producing of mRNA vaccines it is important to use an appropriate vector and method of delivery of the vaccine to the body. Recent years a lot of interest has been seen in using dendritic cells as a vector. Ugur Sahin and his associates were the first to create procedures for creating personalized mRNA mutanomic vaccines. Apart from mutanomes, miRNA - the type of interference RNAs regulating gene expression - played a role in the development of mRNA vaccines. It has been shown that miRNA dysregulation is observed in some cancers and plays a role in invasion, angiogenesis, apoptosis, avoidance of immune destruction or sensitivity to growth factors. Many of the functions of LncRNA affect gene expression by regulating chromatin function, affecting the stability and translation of cytoplasmic mRNA, and signaling pathways, may ultimately lead to cancer formation - and also can be used in anti-cancer therapy and as sensitive biomarkers. These discoveries led to the rapid development of RNA-based anti-cancer therapies and the emergence of the first therapeutics. In this review, we present the use of RNA in anti-cancer therapies and the review of thrapies.